2019
DOI: 10.1186/s12958-019-0452-4
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the lower serum anti-Müllerian hormone threshold for ovarian stimulation prior to in-vitro fertilization using the Elecsys® AMH assay: a prospective observational study

Abstract: BackgroundIn assisted reproductive technology, prediction of treatment failure remains a great challenge. The development of more sensitive assays for measuring anti-Müllerian hormone (AMH) has allowed for the possibility to investigate if a lower threshold of AMH can be established predicting very limited or no response to maximal ovarian stimulation.MethodsA prospective observational multicenter study of 107 women, < 40 years of age with regular menstrual cycle and serum AMH levels ≤ 12 pmol/L, treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…It has been reported that very low values of AMH (1.5 pmol/L, which is equivalent to 0.21 ng/mL [15]) for Elecsys-AMH can predict cycle cancellation, and the cut-off value of Elecsys-AMH for a low oocyte yield (defined as ≤ 3 oocytes) was 0.56 ng/mL [29]. That result also confirmed that the cut-off value of Elecsys-AMH was somewhat higher than that of our study.…”
Section: Table 3 the Equations Between Serum Amh Level And Four Stimu...mentioning
confidence: 99%
“…It has been reported that very low values of AMH (1.5 pmol/L, which is equivalent to 0.21 ng/mL [15]) for Elecsys-AMH can predict cycle cancellation, and the cut-off value of Elecsys-AMH for a low oocyte yield (defined as ≤ 3 oocytes) was 0.56 ng/mL [29]. That result also confirmed that the cut-off value of Elecsys-AMH was somewhat higher than that of our study.…”
Section: Table 3 the Equations Between Serum Amh Level And Four Stimu...mentioning
confidence: 99%